2019
DOI: 10.1021/acsomega.9b00482
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Layered Materials for Multivalent Ion Batteries

Abstract: Batteries based on multivalent ion (such as Al 3+ , Ca 2+ , and Mg 2+ ) intercalation materials have attracted extensive research interest due to their impressive capacity improvement and cost reduction compared with Li-ion batteries. However, the materials for state-of-the-art multivalent ion batteries still suffer from drawbacks such as sluggish ion mobility, poor rate performance, and low cyclic stability, bringing challenges for the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…Therefore, aluminum has been proposed as a suitable alternative due to its high earth abundancy which makes it cheaper than other metal‐based batteries. Due to aluminum being a trivalent ion its volumetric capacity is exceptionally high with a value of 8046 mAh/ml which makes it highly attractive for battery applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, aluminum has been proposed as a suitable alternative due to its high earth abundancy which makes it cheaper than other metal‐based batteries. Due to aluminum being a trivalent ion its volumetric capacity is exceptionally high with a value of 8046 mAh/ml which makes it highly attractive for battery applications …”
Section: Introductionmentioning
confidence: 99%
“…Due to aluminum being a trivalent ion its volumetric capacity is exceptionally high with a value of 8046 mAh/ml which makes it highly attractive for battery applications. [9] Compared to other multivalent ion systems such as aqueous magnesium ion batteries [10] very few reports have been published on aqueous aluminum ion batteries (AAIB) irrespective of its high volumetric capacity. However a recent study has indicated that this is a promising battery technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, material explorations using computational screening have assisted in the identification of promising candidates using high-throughput material databases based on first principles calculations. [24][25][26][27] Promising materials were identified for coatings at the interface of solid electrolytes, 28,29 cathode materials, [30][31][32][33][34] anode materials, 35,36 solid-state electrolyte, 37 Mg battery electrolytes, 38 photo-catalysts, 39 and fuel cell electrodes. 40 Our earlier works also presented novel and promising anode materials for SIBs using high-throughput screening.…”
Section: Introductionmentioning
confidence: 99%
“…While these repositories primarily contain data on bulk materials, two different datasets containing DFT-computed properties for 2D materials were also published recently (Haastrup et al, 2018;Zhou et al, 2019). Knowledge stored in these repositories has then been mined to screen materials for diverse applications (Zhang et al, 2018;Singh et al, 2019;Zhang et al, 2019). In addition, machine learning models have also been trained using data from these repositories to predict properties of novel materials (Ahmad et al, 2018;Xie and Grossman, 2018;Ye et al, 2018;Joshi et al, 2019;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%